(untitled) (One Health & Risk Management, 2021)
Introduction. Adolescents and teenagers aged between 10 and 18 years make up almost a quarter of the total population of the Republic of Moldova. Nowadays, like never before, they are exposed to an extremely big number of risk factors that have a negative influence on their lifestyle. The number of healthy children that attend school has decreased about 3 times in the last decade, resulting from the failure to comply with lifestyle and other life-threatening activities. The major culprits of diseases are considered some wide-spread hazards like: sedentary life, irrational nutrition, smoking, excessive alcohol consumption, drugs, psychosocial stress – factors that could be avoided, yet are usually promoted in what we call today „lifestyle of each individual”. It’s obvious that children’s health represents one of the major current problems worldwide. Material and methods. The study was conducted during the years 2020-2021 on 72 students, of which 23.6% – elementary school, 38.88% – middle school, 37.49% – high school children. 63% were female and 37% – male. In order to assess the risk factors, a questionnaire with 32 questions divided in a few compartments was designed. Results. The questionnaire was completed by 72 students, aged between 9-18 years. 61.11% of interviewee stated that they are healthy, 36.11% had minor health issues, and 2.78% were convinced that they had serious health problems. The last physical examination was performed by 58.33% in the last 12 months, 30.55% – in the last 24 months and 11.11% stated that they didn’t have a physical examination in more than 36 months. As regarding the unhealthy lifestyle factors viz. smoking: 48.14% males stated that they smoke/tried to smoke and 51.86% denied to have smoked; females were more reserved: 11.11% tried to smoke and 88.89% didn’t try. Among those who consume alcohol: 51.38% consume occasionally, 47.22% don’t consume, 1.38% consume regardless of the occasion; therefore, those who consumed more than a glass of alcohol were up to 10 years – 8.33%, 10-12 years – 8.33%, 13-15 years – 29.16%, 16-18 years –19.44%, and those who consumed less than a glass – 34.73% of cases. Among those informed on sexually transmitted diseases: 43.05% – were informed, 43.05% – partially informed, and 13.89% know nothing about this subject. During the week, the students consume milk and its derivatives – 19.44%; meat, processed foods and fish – 31.95%, fruits and vegetables – 25%, cereal products and dried vegetables – 8.33%, and fast-food – 15.27%. Obesity was found as following: normal weight – 75%, underweight – 11%, overweight – 14%, first and second-degree obesity – 0% of cases. As regarding free time activities: watching TV – 13.88%, surfing the Internet – 44.44%, reading – 12.5%, sports – 11.11%, walking outdoors – 16.67%, other activities – 1.38% of students. The survey on illegal drug use sowed that: 97.3% – never used drugs, 2.7% – stated that they tried to use drugs. Conclusions. Students are daily exposed to many risk factors, which require further studies and strategies for promoting a healthy lifestyle.